Pendidikan Karakter Mahasiswa Dengan Pembelajaran Kitab Bidayatul Hidayah di Universitas Pesantren Tinggi Darul 'Ulum Jombang - Ahmad, Fandy (Yayasan Rahmat Islamiyah, 2024)
The purpose of this study is to explain the principles of character education included in the Bidayatul Hidayah book and to detail how the book is taught at the Universitas Pesantren Tinggi Darul 'Ulum Jombang. Descriptive qualitative research methodology is employed in this study. The study's findings demonstrate that the Bidayatul Hidayah book contains a good number of character education values. These values range from how to treat heart disease to proper behavior toward Allah and other people. The emphasis is on approaching Allah with piety and building positive relationships with other people. Therefore, using this book as a resource for character education is totally permissible. Then regarding the study of the Bidayatul Hidayah book at the Universitas Pesantren Tinggi Darul 'Ulum Jombang, it is the same as universities in general, such as making plans and objectives, evaluation tools and learning media, the only difference is the method used is bandongan the typical Islamic boarding school. The learning process seems conducive and the attitudes of the majority of students reflect the ethics described in the Bidayatul Hidayah book.